Bridging the Gap of Educational Outcomes and Industry Needs: Mapping Marketing Management Occupations Within Indonesian Qualification Framework (IQF) - Surono Surono; Rudhi Achmadi (Syntax Corporation Indonesia, 2025)
This study aims to develop the first occupation map for Marketing Management aligned with the Indonesian Qualification Framework (IQF). It responds to the persistent gap between higher education outcomes and industry skill requirements, particularly in digital marketing, data analytics, and strategic innovation. Using the Rapid Assessment Process[A1] [A2] (RAP) through in-depth interviews, focus group discussions, and document analysis, the research identified 47 distinct occupations spanning from entry-level roles such as Retail Assistant to senior executive positions like Chief Marketing Officer. The findings reveal that most occupations have yet to be supported by competency standards, highlighting substantial misalignment between educational programs and workforce expectations. This gap underscores the urgency of embedding industry-driven competencies into curricula and developing flexible training and certification pathways. The occupation map provides a strategic framework for policymakers, educational institutions, and industry stakeholders to redesign curricula, guide recruitment, and shape professional development initiatives. By systematically integrating marketing occupations into the IQF, this research contributes a pioneering reference for Indonesia that strengthens graduate employability, supports workforce planning, and enhances global competitiveness in line with ASEAN Mutual Recognition Arrangements (MRA) and the World Economic Forum's call for future-ready skills.